Methane conversion in low-temperature plasma; High Energy Chemistry; Vol. 43, iss. 3 - Pushkarev A. I. Aleksandr Ivanovich; Zhu A. M.; Li X. S.; Sazonov R. V. Roman Vladimirovich (2009, 2009)
Title screen